Prognostic Value of Protocadherin10 (PCDH10) Methylation in Serum of Prostate Cancer Patients - Deng, Qiu-Kui (Med Sci Monit, 2016)
BACKGROUND: Prostate cancer is a heterogeneous malignancy with outcome difficult to predict. Currently, there is an urgent need to identify novel biomarkers that can accurately predict patient outcome and improve the treatment strategy. The aim of this study was to investigate the methylation status of PCDH10 in serum of prostate cancer patients and its potential relevance to clinicopathological features and prognosis. MATERIAL/METHODS: The methylation status of PCDH10 in serum of 171 primary prostate cancer patients and 65 controls was evaluated by methylation-specific PCR (MSP), after which the relationship between PCDH10 methylation and clinicopathologic features was evaluated. Kaplan-Meier survival analysis and Cox analysis were used to evaluate the correlation between PCDH10 methylation and prognosis. RESULTS: PCDH10 methylation occurred frequently in serum of prostate cancer patients. Moreover, PCDH10 methylation was significantly associated with higher preoperative PSA level, advanced clinical stage, higher Gleason score, lymph node metastasis, and biochemical recurrence (BCR). In addition, patients with methylated PCDH10 had shorter BCR-free survival and overall survival than patients with unmethylated PCDH10. Univariate and multivariate Cox proportional hazards model analysis indicated that PCDH10 methylation in serum is an independent predictor of worse BCR-free survival and overall survival. CONCLUSIONS: PCDH10 methylation in serum is a potential prognostic biomarker for prostate cancer.